Effect of Personality and Interpersonal Communication on Organizational Commitment - Ahmad Syaekhu (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
One of the organizational resources that has an important role in achieving its objectives is human resources both in the private sector and the public sector. This study aims to: 1) Know how much influence the personality variables (Neuroticism, Extraversion, Openness to Experience, Agreeableness, Conscientiousness) and interpersonal communication have an influence on organizational commitment in the office of the South Sulawesi Provincial Environment Agency. 2) Knowing, among the variables of Neuroticism, Extraversion, Openness to Experience, Agreeableness, Conscientiousness, and interpersonal communication, which variable is the dominant influence on Organizational commitment at the office of the Environment Agency of South Sulawesi Province. The analytical method used is a multiple linear analysis method which is also supported by descriptive analysis. The results showed that: there was a positive and significant influence between personality variables on interpersonal communication on organizational commitment at the office of the South Sulawesi Provincial Environment Agency.